A new information hiding method for audio signals - Avci, Derya; Tuncer, Turker; Avci, Engin (Institute of Electrical and Electronics Engineers Inc., 2018)
Transparency, durability and capacity are the performance criteria of data hiding algorithms. In this study, data hiding was performed for the audio data. The most commonly used frequency conversion is Discrete Wavelet Transform (ADD). In this study, high pass filter coefficients were obtained by using ADD. Then the LSB method was applied to these coefficients. The transparency and capacity of the multilevel ADD-LSB method are measured and statistical results are obtained. © 2018 IEEE.
6th International Symposium on Digital Forensic and Security, ISDFS 2018 -- 22 March 2018 through 25 March 2018 -- Antalya -- 136277
Keywords: ADD; Audio Processing; Audio Stegonography; Data Hiding; Information Security